Location-Based Analysis of Household Internet Access Trends in Indonesia Using Chi-Square Analysis - Putri, Novita Yulia; Veronica, Kristy; Renaldo, Nicholas; Tanjung, Amries Rusli; Panjaitan, Harry Patuan; Junaedi, Achmad Tavip; Nyoto, Nyoto; Purnama, Intan; Koto, Jaswar; Jahrizal, Jahrizal (Reflection: Education and Pedagogical Insights, 2025)
This study examines the percentage of Indonesian households accessing the internet in the past three months, disaggregated by location, during the period 2015–2017. Using secondary data from the National Socio-Economic Survey (SUSENAS) conducted by the Central Statistics Agency (BPS), the study applies descriptive statistics to identify access patterns and chi-square tests to evaluate potential relationships between household conditions and internet access location. The findings show a steady increase in household internet access over the three-year period, with home-based access emerging as the most dominant and growing mode of connectivity. Conversely, access via mobile vehicles declined, while internet use at workplaces and public facilities remained low. Chi-square analysis indicates no significant relationship between household conditions and access location. These results highlight the increasing reliance on household internet access and its potential role in supporting learning and digital literacy in Indonesia. However, persistent disparities across regions and socio-economic groups suggest that policies must go beyond infrastructure expansion to address issues of affordability, inclusiveness, and digital literacy. This study contributes to the literature on digital inclusion and provides implications for policymakers, educators, and stakeholders in advancing equitable access to education in the digital age.